PENGARUH PENERAPAN AKUNTANSI LINGKUNGAN - Andriandita Wijayanto; Eko Winarni; Dewi Siti Mahmudah (Yos Soedarso Economic Journal (YEJ), 2021)
Environmental accounting has long been a concern of accountants, the concept of environmental accounting has actually started to develop since 1970 in Europe and increasingly developed in Indonesia in 1990. Environmental Accounting is a term related to the policy of incorporating environmental costs into the environment. the accounting practices of companies or government agencies. Environmental accounting is a term used in different contextsKeywords: Environmental Accounting